Towards a health promoting University: an exploratory study of the University of Cape Town - Mukoma, Wanjiru (Department of Sociology, 2020)
Drawing on developments in the public health field, this exploratory study applies the ideas of Health Promotion (HP) to the University of Cape Town (UCT). It defines UCT as a setting within which HP can and should take place. Following the World Health Organisation (WHO), health is seen as encompassing physical, mental, social, and other environmental factors (WHO, 1978). Sociological perspectives that acknowledge the relationship between social action/behaviour and the social context, hence the relationship between students' wellbeing and the UCT environment are employed. Data and information for this study were collected through focus group discussions, in-depth interviews, participant observation, and a sample of information gathered by first year sociology students. The fear of failure, housing problems, limited social integration, and availability of cigarettes and junk food on campus were found to be some of the factors that influence and constrain students' weIIbeing. It was also found wellbeing is not an explicit consideration in the university plans and policies, even though implicitly these are meant to enhance wellbeing. Strategies to promote health in UCT need to be guided by a commitment to wellbeing in the university's policies. This thesis recommends that the university be required to pass a 'wellbeing test'.